Hubungan Karakteristik Individu dan Daktor Kebutuhan dengan Pemanfaatan Prolanis pada Penderita Hipertensi di Puskesmas Padang Bulan - Siregar, Aldita Ronariski; Nasution, Siti Khadijah; Juanita, Juanita (Universitas Malahayati, 2024)
Introduction: The achievement of the Minimum Service Standards for Hypertension Patients at the Padang Bulan Health Center in 2023 is 43.2 percent. The number of hypertensive patients is increasing every year and the number of cases in 2023 is 8324 cases. Based on a preliminary survey, it was found that the reason 10 hypertensive patients did not moABSTRACT The achievement of the Minimum Service Standards for Hypertension Patients at the Padang Bulan Health Center in 2023 is 43.2 percent. The number of hypertensive patients is increasing every year and the number of cases in 2023 is 8324 cases. Based on a preliminary survey, it was found that the reason 10 hypertensive patients did not monitor their health status regularly was because they were lazy and did not know the function of the prolanis. The purpose of this study is to see the relationship between individual characteristics and needs factors with the use of prolanis in hypertensive patients at the Padang Bulan Health Center. This type of research is quantitative with a cross sectional design. This study was conducted in the working area of the Padang Bulan Health Center on 100 hypertensive patients. The data analysis used for bivariate analysis used the ¬chi-sqaure test. The study found that hypertension affects 67 people, 95 people with high education levels, 42 people with high education levels, 36 people working, and 27 people with a medical certificate. Variables in the relationship between hypertension and education levels were found. Hypertension patients with high education levels and high education levels used hypertension (56.7%), high education levels (59.5%), high education levels (60%), high education levels (60%), high education levels (50%), and high education levels (55.6%) in the study. A significant relationship was found between hypertension needs and education needs in the study. There is a relationship between education level and need factors with the use of prolanis in hypertensive patients at the Padang Bulan Health Center. Keywords: Prolanis, Utilization, Hypertension, Health Center ABSTRAK Capaian Standar Pelayanan Minimal Penderita Hipertensi di Puskesmas Padang Bulan tahun 2023 sebesar 43,2 persen. Jumlah pasien hipertensi mengalami peningkatan setiap tahun dan jumlah kasus pada tahun 2023 adalah 8324 kasus. Berdasarkan survei pendahuluan ditemukan bahwa alasan 10 orang penderita hipertensi yang tidak melakukan pemantauan status kesehatan secara rutin dikarenakan malas dan tidak tahu fungsi prolanis. Tujuan penelitian ini adalah untuk melihat hubungan karakteristik individu dan faktor kebutuhan dengan pemanfaatan prolanis pada penderi hipertensi di Puskesmas Padang Bulan. Jenis penelitian ini adalah kuantitatif dengan desain cross sectional. Penelitian inidilakukan di wilayah kerja Puskesmas Padang Bulan pada 100 penderita hipertensi. Analisis data yang digunakan analisis bivariat menggunakan uji chi-sqaure. Studi tersebut menemukan bahwa hipertensi menyerang 67 orang, 95 orang dengan tingkat pendidikan tinggi, 42 orang dengan tingkat pendidikan tinggi, 36 orang bekerja, dan 27 orang dengan sertifikat medis. Variabel dalam hubungan antara hipertensi dan tingkat pendidikan ditemukan. Pasien hipertensi dengan tingkat pendidikan tinggi dan tingkat pendidikan tinggi menggunakan hipertensi (56,7%), tingkat pendidikan tinggi (59,5%), tingkat pendidikan tinggi (60%), tingkat pendidikan tinggi (60%), tingkat pendidikan tinggi (50%), dan tingkat pendidikan tinggi (55,6%) dalam penelitian ini. Hubungan yang signifikan ditemukan antara kebutuhan hipertensi dan kebutuhan pendidikan dalam penelitian ini. Ada hubungan tingkat pendidikan dan faktor kebutuhan dengan pemanfaatan prolanis pada penderita hipertensi di Puskesmas Padang Bulan. Kata Kunci: Prolanis, Pemanfaatan, Hipertensi, Puskesmasnitor their health status regularly was because they were lazy and did not know the function of the prolanis.Purpose: The purpose of this study is to see the relationship between individual characteristics and needs factors with the use of prolanis in hypertensive patients at the Padang Bulan Health Center.Method: This type of research is quantitative with a cross sectional design. This study was conducted in the working area of the Padang Bulan Health Center on 100 hypertensive patients. The data analysis used for bivariate analysis used the ¬chi-sqaure test.Result: The study found that hypertension affects 67 people, 95 people with high education levels, 42 people with high education levels, 36 people working, and 27 people with a medical certificate. Variables in the relationship between hypertension and education levels were found. Hypertension patients with high education levels and high education levels used hypertension (56.7%), high education levels (59.5%), high education levels (60%), high education levels (60%), high education levels (50%), and high education levels (55.6%) in the study. A significant relationship was found between hypertension needs and education needs in the study.Conclusion: There is a relationship between education level and need factors with the use of prolanis in hypertensive patients at the Padang Bulan Health Center. Keywords: prolanis, utilization, hypertension, health center